THERMAL PREFERENCES OF DAIRY COWS HOUSEDIN FREESTALL CONFINEMENT SYSTEM - Souza, Silvia R. L.; Nääs, Irenilza A.; Moura, Daniella J. (Revista Brasileira de Engenharia de Biossistemas, 2007)
The differences in the rearing microclimate may promote changes in the animal behavior,when its thermal preference of higher priority is shown. Conventional measurementsare not precise leading to eventual error in the results interpretation. This present research had the objective to identify with precision the thermal preferences of dairy cows rearedin freestall barn, as function of the local environment. The experiment was conduced ina commercial dairy farm located at São Pedro, SP, where the cows were monitoredthrough videos taken with six colored high resolution video cameras, and 120 degreeslens for registering the local occupancy. Visual observations were made afterwardsusing the videos for analyzing the behavior. The barn was divided into 18 virtual quadrantsfor the mapping of the ambient temperature, relative humidity and air velocity distribution,and the data were processed using the software Surfer® for analyzing its homogeneity.The results from the multivariable analysis using the observed behavioral data showedin the graph of Main Components the cows preference considered important for obtainingan expressive vector answer when affected by the rearing environment: drinking water,eating, and laying down on bedding. The environmental distribution inside the barn wasnot homogeneous, and varied as function of the use of acclimatization equipments. Itwas concluded that the cows had priority preference by the places where the environmentis milder, and the air speed is higher.